CORPORATE WORKING CAPITAL STRATEGIES IN EUROPE: A CROSS-INDUSTRY AND CROSS-COUNTRY ANALYSIS - Koralun-Bereźnicka, Julia (European Scientific Journal, ESJ, 2013)
Corporate finance literature traditionally abounds in both theoretical discussion and empirical research concerning financing and long term investment decisions. Managing short term resources seems a much less remarkable issue, despite their considerable share in a firm’s balance sheet and their significance for corporate health. This article provides insights into the working capital strategies in the European Union perspective from the point of view of two factors affecting this capital. The determinants considered in the study include two external factors, namely the country and industry where a company operates. The theoretical part of the paper contains literature review reflecting the impact of the selected factors on working capital management. The empirical analysis covers groups of firms in nine EU countries and thirteen industries in the period 2000-2010. Corporate working capital is characterised by several financial ratios The objects treated as countries, industries and industries in countries are categorised into three strategic groups (aggressive, neutral and conservative) according to the linear ranking based on the aggregated taxonomic measure.